Is it true that plant‐derived polyphenols are always beneficial for the human?In vitrostudy onLeonurus cardiacaextract properties in the context of the pathogenesis ofStaphylococcus aureusinfections. Issue 10 (18th October 2016) - Micota, Bartłomiej; Sadowska, Beata; Podsędek, Anna; Paszkiewicz, Małgorzata; Sosnowska, Dorota; Różalska, Barbara
Abstract : N/A: The aim of the study was to determine whether Leonurus cardiaca L. herb extract (LCE) used at subinhibitory concentration modifies the characteristics of Staphylococcus aureus, which is important in the pathogenesis of invasive infections originating from the bloodstream, in a way favourable for the human host. Polyphenol‐rich LCE, a common ingredient in pharmaceutical products used for various cardiovascular and nervous system disorders, had shown interesting antibacterial and antibiofilm properties in our previous studies. Our current findings indicate that the following S. aureus characteristics decreased, depending on the LCE concentration: (i) formation of aggregates in plasma, (ii) adherence to a fibrin‐coated surface, (iii) staphylocoagulase‐dependent plasma clotting, (iv) bacterial survival in whole human blood in an ex vivo model, (v) expression of cell surface protein A and (vi) synthesis of α‐toxin. However, staphylococcal tolerance to exogenous hydrogen peroxide was enhanced after pre‐incubation with LCE, possibly due to the increased activity of bacterial antioxidant enzymes, a possibility confirmed by the higher production of superoxide dismutase and slightly higher production of catalase. The use of LCE at sub‐MIC in in vitro and ex vivo models resulted in the weakening of some important staphylococcal immunoprotective attributes but the strengthening of such virulence factors as those responsible for oxidative stress tolerance. Some of these results and the fact that LCE has direct anticoagulant properties, reflected in a reduced thrombin‐dependent fibrinogen polymerization rate, suggest a risk of adverse effects, which could be important in the context of S. aureus survival in the host.